Career Choices among Nursing Students: Differences between Freshmen and Interns - Ni Putu Wulan Purnama Sari (Jurnal Pendidikan Keperawatan Indonesia, 2020)
ABSTRACT Career selection is one of the most important decisions that an individual makes in his life and is a core task of the late stages of adolescent development in the process of developing self-identity. This study aimed to describe the career choices of nursing students and analyze the differences between freshmen and interns. This cross-sectional study involved 110 and 66 freshmen and interns respectively in two private nursing colleges with “B” accreditation predicate (n=176). Questionnaire of Survey on Career Choice was used in data collection. Descriptive statistic test was used in data analysis. Results showed that most freshmen chose two career choice alternatives (38.18%), but most interns were determined to choose only one alternative (42.42%). There were two most popular career choices among nursing students, such as: nurse practitioner (45.45% totally) and continuing education to be a Master/Specialist of Nursing (33.52% totally). The career intention to be a nurse practitioner in most respondents was referred to civil servant, both in clinical or community work places (59.66% totally). The most popular nursing fields were pediatric nursing in freshmen and psychiatric nursing in interns (34.55% and 25.76% respectively). Strengthening the attitude of love for nursing profession needs to be fostered early in the beginning of college life, so that career choice as a nurse practitioner after finishing the internship program can be maintained.